The Art of Observation in Homoeopathy (Homoeopathy for All, 2025)
Accurate observation is the  cornerstone of homoeopathic  practice. In homoeopathy the  selection of remedy mainly depends  upon the observation. For fine  prescription there is the need of  trained unprejudiced observer who  select the remedy on the basis of keen  observation. Samuel Hahnemann  emphasized that a physician must  train the senses to perceive, record,  and interpret even the most delicate  signs of disease and medicinal  action. Dr. Stuart Close further  refined this by outlining how bedside  observations—mental, physical, and  environmental—become essential  for individualizing a case. This  article explores the philosophy of  observation, its clinical application,  and its representation in standard  repertories such as Kent and  Murphy. The aim is to highlight how  observation bridges the patient’s  unique expression of illness with the  choice of the similimum
Keywords: Observation; Hahnemann; Stuart Close; Repertory; Kent; Murphy; Homoeopathy; Case taking